Założenie o racjonalności w ekonomii marksistowskiej i marksowskiej - Nowak, Leszek (Wydział Prawa i Administracji UAM, 1972)
The aim of this article is 1) to present several conceptions of assumption of rationality in to-day's publications on methodology of economics, 2) to state which of the conceptions are accepted by representative Marxist economists in their methodological consideration and 3) to find if the approaches correspond to the methodological part that the assumption of rationality plays in the economic theory of Karl Marx.
Assumption of Rationality in Marxist and Marxian Economics